2016
DOI: 10.1590/s1679-45082016ao3640
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Thyroid Imaging Reporting and Data System [TI-RADS] and fine needle aspiration: experience in 1,000 nodules

Abstract: Objective To correlate the Thyroid Imaging Reporting and Data System (TI-RADS) and the Bethesda system in reporting cytopathology in 1,000 thyroid nodules.Methods A retrospective study conducted from November 2011 to February 2014 that evaluated 1,000 thyroid nodules of 906 patients who underwent ultrasound exam and fine needle aspiration.Results A significant association was found between the TI-RADS outcome and Bethesda classification (p<0.001). Most individuals with TI-RADS 2 or 3 had Bethesda 2 result (95.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Um achado inesperado em nosso estudo foi a parcela de nódulos Bethesda I (citopatologia insatisfatória), representando 24,4% dos nódulos puncionados, sendo superior ao encontrado na literatura (20)(21)(22) . Em contrapartida, as características epidemiológicas foram semelhantes ao encontrado em outros artigos, com uma média de idade de 53,2 anos ± 13,4 anos (9,(22)(23)(24)(25) , tamanho médio do nódulo de 2,1 cm (23,26) e predomínio do sexo feminino (9,(22)(23)(24) .…”
Section: Discussionunclassified
“…Um achado inesperado em nosso estudo foi a parcela de nódulos Bethesda I (citopatologia insatisfatória), representando 24,4% dos nódulos puncionados, sendo superior ao encontrado na literatura (20)(21)(22) . Em contrapartida, as características epidemiológicas foram semelhantes ao encontrado em outros artigos, com uma média de idade de 53,2 anos ± 13,4 anos (9,(22)(23)(24)(25) , tamanho médio do nódulo de 2,1 cm (23,26) e predomínio do sexo feminino (9,(22)(23)(24) .…”
Section: Discussionunclassified
“…The included studies consisted mainly of prospective (n=4) and retrospective studies (n=4) followed by reviews/guidelines (n=3) and a multi-center study (n=1). In terms of population characteristics, four larges studies consisted of 3,315 participants (3,822 nodules), 2921 participants (3,980 nodules), 1,241 participants (1,293 nodules), and 906 participants (1,000 nodules) [15,16,20,21]. Five comparatively small studies included 238 participants (272 nodules), 105 participants (nodules not reported), 100 participants (157 nodules), 100 participants (nodules not reported), and 84 participants (87 nodules) [17-19, 22,23].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five comparatively small studies included 238 participants (272 nodules), 105 participants (nodules not reported), 100 participants (157 nodules), 100 participants (nodules not reported), and 84 participants (87 nodules) [17-19, 22,23]. A total of 9,010 participants (10,611 nodules) were reported from all studies [14][15][16][17][18][19][20][21][22][23][24][25]. The proportion of participants who were male (nodules from male participants) reported from studies ranged from 14% to 33% (20-29%) [15][16][17][18][19]22,23].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the already established Breast Imaging Reporting and Data System (BI‐RADS) for breast lesions, a Thyroid Imaging Reporting and Data System (TI‐RADS) was introduced to the field of thyroid ultrasound imaging in 2009 by Horvath, et al 3 Various formats of TI‐RADS have been applied in different studies performed outside of the United States. 4‐7 The American College of Radiology (ACR) published the white paper for its TI‐RADS in 2017. 8 The present study was initiated right before the publication of ACR's TI‐RADS.…”
Section: Introductionmentioning
confidence: 99%